Wastewater treatment by immobilised cell systems - Jameel, Ahmad Tariq; Abass Olanrewaju, Alade (IIUM Press, 2011)
The immobilization of whole cells is an important technique which provides alternative solution in the field of wastewater treatment for the purification of wastewater contaminated with various materials, such as organic compounds, inorganic compounds, metals, and so on. The immobilized cells are biocatalysts which can easily be separated from treated water without a setting step and such can be repeatedly used without washing out from the systems. The processes using immobilized cells have been studied and applied to practical treatment systems. An effective way of removing ammonia nitrogen from aqueous solutions is the utilization of immobilized cells because of high cell concentration, long retention time of biomass in the system, rapid separation of cells from liquid and ability to scale up the process. These immobilized catalyst systems are therefore proposed as potential methods for the treatment of various types of wastewater from low to high strength.